(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Ecotourism-oriented homestays are a significant driving force for rural revitalization. The landscape is instrumental in distinguishing homestays from one another and enhancing their allure, contributing to cultural heritage and sustainable economic development. However, the current homestay development landscape is marred by several challenges, including a lack of diversity in landscapes, a disconnect from local cultural roots, overdevelopment, ecological protection imbalances, a dearth of interactive experiences, and unregulated service standards. This study uses six representative cases in Zhejiang Province, China, integrating publicly accessible government environmental performance data, tourist review texts sourced from online travel platforms, and insights gleaned from semi-structured expert interviews. A multi-dimensional evaluation framework is established based on Environmental, Social, and Governance (ESG) principles. Quantitative text semantic analysis techniques were applied to parse the review texts, subsequently utilizing statistical methods to ascertain the relative importance of dimensions and indicators and explore their relationships. A significant correlation was observed between the prevalence of ecologically favorable language in user reviews and official environmental assessment scores. The frequency of culturally specific references in guest reviews exhibited a statistically significant positive correlation with tourist ratings. Drawing upon the preceding analysis, the study formulates landscape design guidelines that emphasize green technology, cultural empowerment, and social identity.